2020
DOI: 10.24018/ejmed.2020.2.6.554
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Learning During Clinical Rotations in the Emergency Department: The Perspective of Students in a Public Sector Institute of a Developing Country

Abstract: Background: Clinical learning is the crux of medical education. Students perceive many barriers to effective clinical learning due to transition, poor supervision, and lack of orientation. There is an urgent need for recommendations to alleviate these barriers and improve the quality of medical education in a public sector institute of a developing country. Aims: The study aims to identify the barriers in clinical learning perceived by the students during their clinical rotations in emergency. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Another study from Pakistan highlights the impediments faced during clinical learning in the form of suboptimal clinical rotation planning, insufficient clinical orientation, poor supervision and lack of resources with a crippled feedback delivery system acting as barriers to effective clinical learning. However, due to a lack of adequate clinical rotation planning, students are distanced from several medical fields [20]. Similarly, a study from Saudi Arabia found that interest in neurosurgery as a specialization can be strengthened by enhancing the exposure of students and interns to the specialty during their medical school years.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Pakistan highlights the impediments faced during clinical learning in the form of suboptimal clinical rotation planning, insufficient clinical orientation, poor supervision and lack of resources with a crippled feedback delivery system acting as barriers to effective clinical learning. However, due to a lack of adequate clinical rotation planning, students are distanced from several medical fields [20]. Similarly, a study from Saudi Arabia found that interest in neurosurgery as a specialization can be strengthened by enhancing the exposure of students and interns to the specialty during their medical school years.…”
Section: Discussionmentioning
confidence: 99%